Calcination-free preparation method of sodium ferric sulfate positive electrode material of sodium ion battery
Through the calcin-free preparation method, the sodium iron sulfate positive electrode material is prepared by high-energy ball milling technology, which solves the problems of complex, low efficiency and high cost in the traditional synthesis process, and realizes high-efficiency and low energy consumption material preparation, which is suitable for mass production.
Patent Information
- Application Number
- CN202411609017.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing ferrosulfate positive electrode material has complex synthesis process, low production efficiency and high production cost.
Using the calcin-free preparation method, sodium iron sulfate positive electrode material is prepared by mixing sodium, iron, carbon coated material and flux and undergoing high-energy ball milling.
This method does not require inert atmosphere calcination, the material synthesis time is short, the production efficiency is high, the energy consumption is low, the cost is low, and the process is simple and easy to achieve industrialization.
Smart Images

Figure CN119430294A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery material preparation, and specifically relates to a calcination-free preparation method and application of sodium iron sulfate positive electrode material for sodium ion batteries. Background Art
[0002] Sodium-ion batteries have become one of the most promising chemical power sources in the post-lithium-ion battery era due to their uniform distribution of sodium resources, low cost, and similar electrochemical properties to lithium-ion batteries. However, the larger ionic radius and heavier atomic mass compared to lithium ions limit the rapid movement of sodium ions in electrode materials, resulting in relatively slow reaction kinetics and low energy density in sodium-ion batteries. As a key component affecting the final performance and cost of batteries, the key to achieving the next generation of batteries lies in the development of high-quality cathodes that combine low cost and high energy density. In view of this, developing new types of cathode materials by improving battery voltage and stable capacity is the best way to develop sodium-ion batteries. Among the many sodium-ion battery cathode materials, sodium iron sulfate materials exhibit outstanding high redox potentials due to the strong inductive effect of sulfate. At the same time, the low raw material cost and environmental friendliness make this material show comprehensive superiority and broad application prospects.
[0003] Sodium iron sulfate cathode materials are generally prepared from sodium sulfate and ferrous sulfate using sol-gel method, spray drying method or solid phase ball milling method. 2+ The presence of makes it very sensitive to water and oxygen, and the use of liquid phase synthesis methods such as sol-gel and spray drying has inherent disadvantages. Relatively speaking, the solid phase ball milling method not only effectively eliminates the interference of water and air on the material, but is also more conducive to scale-up synthesis. However, the traditional solid phase ball milling method usually requires a long ball milling and inert atmosphere calcination time, low production efficiency and high cost. Therefore, it is of great significance to provide a more efficient and convenient method for preparing sodium iron sulfate positive electrode materials to reduce the time and cost of material synthesis. Summary of the invention
[0004] The present invention aims to solve the problems of complex synthesis process, low production efficiency and high production cost of existing sodium ferric sulfate positive electrode materials, and provide a calcination-free preparation method of sodium ferric sulfate positive electrode materials for sodium ion batteries. The method is convenient, efficient, low in energy consumption, and can be applied to batch material synthesis.
[0005] The calcination-free preparation method of the sodium iron sulfate positive electrode material for a sodium ion battery of the present invention is carried out according to the following steps:
[0006] Step 1: mixing a sodium source, an iron source, and a carbon-coated material, or adding a flux thereto, to obtain a mixture;
[0007] Step 2: subjecting the mixture to high-energy ball milling to obtain sodium iron sulfate positive electrode material.
[0008] Furthermore, the sodium source in step 1 is anhydrous sodium sulfate and / or sodium sulfate decahydrate.
[0009] Furthermore, the iron source described in step one is one or more of anhydrous ferrous sulfate, ferrous sulfate monohydrate and ferrous sulfate heptahydrate.
[0010] Furthermore, the carbon coating material described in step 1 is one or more of conductive carbon black, acetylene black, Ketjen black, graphene, redox graphene and carbon nanotubes.
[0011] Furthermore, the flux described in step 1 is a halide flux, and the halide flux is one or more of aluminum fluoride, aluminum chloride, magnesium fluoride, magnesium chloride, lithium fluoride, lithium chloride, sodium fluoride, sodium chloride, potassium fluoride, potassium chloride, barium fluoride, barium chloride, calcium fluoride, calcium chloride, stannous chloride, stannous fluoride, tin chloride, tin fluoride, gallium chloride, gallium fluoride, ammonium fluoride and ammonium chloride. The halide flux has a low melting point or can produce molten material during heating. The purpose of adding the flux is mainly to reduce the reaction temperature so that the material is more easily generated through mechanical heat release of ball milling.
[0012] Furthermore, the molar ratio of the sodium source to the iron source in step 1 is (1-2): 1. Too high or too low a molar ratio of the sodium source to the iron source is likely to produce impurities, affecting the performance of the product. Under the molar ratio conditions set by the present invention, the obtained product is purer.
[0013] Furthermore, the flux described in step 1 accounts for 1wt% to 7wt% of the total material. Adding a certain amount of flux to the mixed material formula can effectively reduce the reaction temperature, improve production efficiency and reduce reaction energy consumption, but too high a flux ratio may reduce the purity and discharge specific capacity of the product, so the present invention makes the above limit on the amount of flux added.
[0014] Furthermore, the mass proportion of the carbon coating material in step 1 is 2wt% to 10wt% of the total material. Appropriate carbon addition can effectively improve the electronic conductivity of the material, but in order to minimize the introduction of electrochemically inert carbon components, the present invention makes the above limit on the amount of carbon source added.
[0015] Furthermore, the ball mill described in step 2 is a planetary ball mill, the ball mill speed is 200 rpm to 500 rpm, and the ball mill time is 10 h to 55 h. If the ball mill speed is too slow or the ball mill time is too short, the raw materials will be unevenly mixed, the crushing will not be thorough, and the heat generated in the ball mill jar will be insufficient, resulting in a high impurity content in the product; if the ball mill speed is too fast or the ball mill time is too long, the heat generated in the ball mill jar will be too much, causing the material to be overburned, resulting in impurities or decomposition.
[0016] Furthermore, the ball milling atmosphere in step 2 is an inert atmosphere or air.
[0017] The technical solution of the present invention has the following advantages over the prior art:
[0018] (1) The preparation method of the present invention does not require inert atmosphere calcination, the material synthesis period is short, the production efficiency is high, the energy consumption is low, and the cost is low. In addition, the method has a simple process and is easy to industrialize, and has good economic benefits and operability.
[0019] (2) The preparation method of the present invention can add a certain amount of flux to the raw materials. The flux has a low melting point and can effectively reduce the reaction temperature, making it easier for the material to be generated through the mechanical heat release of ball milling. The added flux can melt in advance during the ball milling process, playing the role of flux and reaction medium, so that the reaction raw materials are fully contacted and mixed, effectively shortening the ball milling time. The added flux can also form a coating layer on the surface of the material to isolate the sodium ferric sulfate material from oxygen and moisture. The added flux has a reducing property, which can effectively prevent Fe in the material from being heated. 2+ The added flux has strong conductivity, which can effectively improve the electronic conductivity of the material and improve the electrochemical properties of the material; the added flux has redox activity, which can further improve the discharge capacity of the positive electrode material. The sodium iron sulfate positive electrode material prepared with stannous chloride as the flux is expressed as Na x Fe y Sn z (SO4)3Cl m / C compound, wherein 2≤x≤3, 1.5≤y≤2, 0<z≤0.40, 0<m≤0.80; the values of x, y, z, and m satisfy the charge balance of the chemical formula. The sodium ferric sulfate positive electrode material of the present invention has a first discharge specific capacity of 79.2-88.3 mAh / g at a rate of 0.1C, a first coulombic efficiency of 87.7%-89.4%, and a discharge median voltage of 3.7-3.8V. The sodium ferric sulfate positive electrode material can be used in the field of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the XRD spectrum of the sodium iron sulfate positive electrode material prepared in Example 1;
[0021] Figure 2 The first charge and discharge curve of the sodium iron sulfate positive electrode material prepared in Example 1 at a rate of 0.1C;
[0022] Figure 3 The first charge and discharge curve of the sodium iron sulfate positive electrode material prepared in Comparative Example 1 at a rate of 0.1C;
[0023] Figure 4 is the XRD spectrum of the sodium iron sulfate positive electrode material prepared in Example 2;
[0024] Figure 5 This is the first charge and discharge curve of the sodium iron sulfate positive electrode material prepared in Example 2 at a rate of 0.1C. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments do not limit the content and protection scope of the present invention. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0026] Example 1: The calcination-free preparation method of the sodium iron sulfate positive electrode material for sodium ion batteries of this embodiment is carried out according to the following steps:
[0027] 1. Take 0.4259 g of sodium sulfate, 0.4562 g of ferrous sulfate, and 0.0557 g of graphene and mix them evenly to obtain a mixture;
[0028] 2. Place the mixture in the ball milling jar of a Laichi PM100 planetary ball mill, fill the jar with nitrogen gas for protection, and ball mill at a speed of 400 rpm for 24 hours. After natural cooling, sodium iron sulfate positive electrode material is obtained.
[0029] The XRD spectrum of the sodium iron sulfate positive electrode material prepared in this example is as follows Figure 1 As shown, from Figure 1 It can be seen that the obtained product maintains the typical sodium iron sulfate structure, but due to the mechanical heat release of ball milling, it is difficult to maintain a high reaction temperature, and there are still some obvious impurity peaks in the product, indicating that the phase purity of the product is still not high enough.
[0030] The sodium ferric sulfate positive electrode material of the sodium ion battery prepared in this embodiment is mixed with the conductive agent Super P and the binder polyvinylidene fluoride dissolved in N-methylpyrrolidone in a mass ratio of 7:2:1, and coated on the current collector aluminum foil to prepare a sodium ferric sulfate electrode. The obtained sodium ferric sulfate positive electrode and the metal sodium negative electrode are assembled to simulate a sodium ion battery, and the electrochemical performance test is carried out in the range of 2.0 to 4.5V. The first charge and discharge curve of the sodium ferric sulfate positive electrode material prepared in Example 1 at a rate of 0.1C is shown as follows: Figure 2 As shown, from Figure 2 It can be seen that the first discharge specific capacity at a rate of 0.1C is 79.2mAh / g, the coulombic efficiency is 87.7%, and the median discharge voltage is 3.7V.
[0031] Comparative Example 1: This comparative example is different from Example 1 in that graphene carbon is not added in step 1, and the other steps and parameters are the same as Example 1 to obtain a sodium iron sulfate positive electrode material.
[0032] Using the same method as in Example 1, the sodium iron sulfate cathode material prepared in the comparative example and the metal sodium anode were assembled into a simulated sodium ion battery, and the electrochemical performance test was carried out in the range of 2.0 to 4.5 V. The first charge and discharge curve of the sodium iron sulfate cathode material obtained at a rate of 0.1 C was as follows: Figure 3 As shown, due to the lack of conductive carbon to improve the electronic conductivity of the material, the electrochemical performance of the material is poor. The first discharge specific capacity at a rate of 0.1C is 54.79mAh / g, the coulombic efficiency is 87.7%, and the median discharge voltage is 3.6V.
[0033] Example 2: The calcination-free preparation method of the sodium iron sulfate positive electrode material for sodium ion batteries of this embodiment is carried out according to the following steps:
[0034] 1. Weigh 0.3435 g of sodium sulfate, 0.5214 g of ferrous sulfate, 0.0464 g of carbon nanotubes and 0.0173 g of stannous chloride, mix well to obtain a mixture;
[0035] 2. Place the mixture in the ball milling jar of a Laichi PM100 planetary ball mill, fill the jar with nitrogen gas for protection, and ball mill at a speed of 400 rpm for 24 hours. After natural cooling, sodium iron sulfate positive electrode material is obtained.
[0036] In this embodiment, stannous chloride is added as a flux, and the chemical formula of the prepared sodium iron sulfate positive electrode material is Na 2.48 Fe 1.76 Sn 0.09 (SO4)3Cl 0.18 / C, its XRD spectrum is as follows Figure 3 As shown, the obtained product exhibits characteristic peaks of sodium ferric sulfate. Since the flux effectively reduces the reaction temperature, the mechanical heat release of the ball milling better maintains the reaction temperature, so that the product has a good crystal state and exhibits a sharper spectral peak shape compared to Example 1.
[0037] Using the same method as in Example 1, the sodium iron sulfate cathode material prepared in the comparative example and the metal sodium anode were assembled into a simulated sodium ion battery, and the electrochemical performance test was carried out in the range of 2.0 to 4.5 V. The first charge and discharge curve of the sodium iron sulfate cathode material obtained at a rate of 0.1 C was as follows: Figure 3 As shown, due to the lack of conductive carbon to improve the electronic conductivity of the material, the electrochemical performance of the material is poor. The first discharge specific capacity at a rate of 0.1C is 54.79mAh / g, the coulombic efficiency is 87.7%, and the median discharge voltage is 3.6V.
[0038] The sodium iron sulfate cathode material prepared in this example was assembled with a metal sodium anode to simulate a sodium ion battery using the same method as in Example 1, and the electrochemical performance was tested in the range of 2.0 to 4.5 V. The first charge and discharge curve of the sodium iron sulfate cathode material prepared in Example 2 at a rate of 0.1 C was as follows: Figure 4 The addition of stannous chloride flux effectively reduces the reaction temperature and improves the electronic conductivity and stability of the material. 2+ The redox activity of the material also further improves the discharge capacity. Therefore, the sodium iron sulfate cathode material prepared in Example 2 exhibits excellent electrochemical performance, with an initial discharge capacity of 88.3 mAh / g at a rate of 0.1 C, an initial coulombic efficiency of 89.4%, and a discharge median voltage of 3.8 V.
[0039] Example 3: The calcination-free preparation method of the sodium iron sulfate positive electrode material for sodium ion batteries of this embodiment is carried out according to the following steps:
[0040] 1. Weigh 0.3435 g of sodium sulfate, 0.5214 g of ferrous sulfate, 0.0464 g of conductive carbon black and 0.0173 g of ammonium chloride, mix well to obtain a mixture;
[0041] 2. Place the mixture in the ball milling jar of a Laichi PM100 planetary ball mill, fill the jar with inert gas for protection, and ball mill at a speed of 350 rpm for 50 hours. After natural cooling, sodium iron sulfate positive electrode material is obtained.
[0042] Using the same method as in Example 1, the sodium iron sulfate positive electrode material prepared in Example 3 and the metallic sodium negative electrode were assembled to simulate a sodium ion battery, and the electrochemical performance was tested in the range of 2.0 to 4.5 V. The obtained positive electrode had a first discharge specific capacity of 83.0 mAh / g at a rate of 0.1 C, a coulombic efficiency of 85.1%, and a discharge median voltage of 3.7 V.
[0043] Example 4: The calcination-free preparation method of the sodium iron sulfate positive electrode material for sodium ion batteries of this embodiment is carried out according to the following steps:
[0044] 1. Weigh 0.3572 g of sodium sulfate, 0.5068 g of ferrous sulfate, 0.0464 g of graphene and 0.0173 g of stannous chloride, mix well to obtain a mixture;
[0045] 2. Place the mixture in the ball milling jar of a Laichi PM100 planetary ball mill, fill the jar with inert gas for protection, and ball mill at a speed of 300 rpm for 48 hours. After natural cooling, sodium iron sulfate positive electrode material is obtained.
[0046] Example 5: The calcination-free preparation method of the sodium iron sulfate positive electrode material for sodium ion batteries of this embodiment is carried out according to the following steps:
[0047] 1. Weigh 0.3435 g of sodium sulfate, 0.5214 g of ferrous sulfate, 0.0464 g of conductive carbon black and 0.0173 g of aluminum fluoride, mix well to obtain a mixture;
[0048] 2. Place the mixture in the ball milling jar of a Lai Chi PM100 planetary ball mill. Fill the jar with air and mill at a speed of 450 rpm for 30 hours. After cooling naturally, obtain the sodium iron sulfate positive electrode material.
[0049] Example 6: The calcination-free preparation method of the sodium iron sulfate positive electrode material for sodium ion batteries of this embodiment is carried out according to the following steps:
[0050] 1. Weigh 0.3267 g of sodium sulfate, 0.5394 g of ferrous sulfate, 0.0464 g of graphene and 0.0173 g of ammonium fluoride, mix well to obtain a mixture;
[0051] 2. Place the mixture in the ball milling jar of a Laichi PM100 planetary ball mill, fill the jar with inert gas for protection, and ball mill at a speed of 500 rpm for 10 hours. After natural cooling, sodium iron sulfate positive electrode material is obtained.
Claims
1. A calcination-free preparation method for sodium iron sulfate positive electrode material of sodium ion battery, characterized in that The method proceeds as follows: Step 1: mixing a sodium source, an iron source, and a carbon-coated material, or adding a flux thereto, to obtain a mixture; Step 2: subjecting the mixture to high-energy ball milling to obtain sodium iron sulfate positive electrode material.
2. The calcination-free preparation method of sodium iron sulfate positive electrode material for sodium ion battery according to claim 1, characterized in that: The sodium source described in step 1 is anhydrous sodium sulfate and / or sodium sulfate decahydrate.
3. The calcination-free preparation method of sodium iron sulfate positive electrode material for sodium ion battery according to claim 1 or 2, characterized in that: The iron source described in step 1 is one or more of anhydrous ferrous sulfate, ferrous sulfate monohydrate and ferrous sulfate heptahydrate.
4. The calcination-free preparation method of a sodium iron sulfate positive electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: The carbon coating material described in step 1 is one or more of conductive carbon black, acetylene black, Ketjen black, graphene, redox graphene and carbon nanotubes.
5. The calcination-free preparation method of sodium iron sulfate positive electrode material for sodium ion battery according to claim 1 or 2, characterized in that: The flux described in step one is one or more of aluminum fluoride, aluminum chloride, magnesium fluoride, magnesium chloride, lithium fluoride, lithium chloride, sodium fluoride, sodium chloride, potassium fluoride, potassium chloride, barium fluoride, barium chloride, calcium fluoride, calcium chloride, stannous chloride, stannous fluoride, stannous chloride, stannous fluoride, gallium chloride, gallium fluoride, ammonium fluoride and ammonium chloride.
6. The calcination-free preparation method of sodium iron sulfate positive electrode material for sodium ion battery according to claim 1 or 2, characterized in that: The molar ratio of the sodium source to the iron source in step 1 is (1-2):
1.
7. The calcination-free preparation method of sodium iron sulfate positive electrode material for sodium ion battery according to claim 1 or 2, characterized in that: The flux described in step 1 accounts for 1wt% to 7wt% of the total material.
8. The calcination-free preparation method of sodium iron sulfate positive electrode material for sodium ion battery according to claim 1 or 2, characterized in that: The mass proportion of the carbon coating material described in step 1 is 2wt% to 10wt% of the total material.
9. The calcination-free preparation method of sodium iron sulfate positive electrode material for sodium ion battery according to claim 1 or 2, characterized in that: The ball mill described in step 2 is a planetary ball mill, the ball milling speed is 200 rpm to 500 rpm, and the ball milling time is 10 h to 55 h.
10. The calcination-free preparation method of sodium iron sulfate positive electrode material for sodium ion battery according to claim 1 or 2, characterized in that: The ball milling atmosphere in step 2 is an inert atmosphere or air.
Citation Information
Patent Citations
High-capacity sodium ferric sulfate positive electrode material as well as preparation method and application thereof
CN117542982A
Composite metal oxide and sodium secondary battery
JP2009209037A
Negative active material and rechargeable lithium battery including same
KR1020250020974A
Cathode material for solid-state electrolyte molten lithium battery
WO2024067659A1